The rheological behavior of ethylene vinyl acetate copolymer/rectorite nanocomposites during the melt extrusion process. (25th April 2016) - Chen, Z.; Yin, C.; Wang, S.; Fu, Q. M.; Deng, Q. R.; Lin, Z. D.; Fu, P.; Zhang, Y.; Wu, J. Y.; Fang, P. F.
Abstract : To optimize the preparation process for ethylene vinyl acetate (EVA)/rectorite nanocomposites during the melt extrusion, the effect of rectorite on the rheological property of molten polymer has been explored in this paper. The dispersion of rectorite in EVA was probed by X‐ray diffraction, and the rheological behaviors of EVA copolymer and EVA/rectorite nanocomposites during the extrusion process were investigated by means of HAAKE minilab. The positron results reveal that introducing the rectorite in EVA matrix increases the interfaces in composites. And the rheological results indicate that the viscosity of EVA and EVA/rectorite nanocomposites in the molten state was influenced by the processing temperature, processing time and shearing rate. For all the samples, the viscosity increases with increasing the shear rate, and decreases with increasing extrusion temperature. Moreover, compared with the pure EVA, the EVA/rectorite nanocomposite presents a lower viscosity at the same processing condition. Copyright © 2016 John Wiley & Sons, Ltd.